2022
DOI: 10.3390/toxins14100687
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in Cereals and Cereal-Based Products: Occurrence, Toxicity, Impact on Human Health, and Their Detoxification and Management Strategies

Abstract: Cereals and cereal-based products are primary sources of nutrition across the world. However, contamination of these foods with aflatoxins (AFs), secondary metabolites produced by several fungal species, has raised serious concerns. AF generation in innate substrates is influenced by several parameters, including the substrate type, fungus species, moisture content, minerals, humidity, temperature, and physical injury to the kernels. Consumption of AF-contaminated cereals and cereal-based products can lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 206 publications
0
11
0
Order By: Relevance
“…Corn is an important component of poultry feed commonly contaminated with Fusarium molds, thus potentially exposing laying hens to trichothecene mycotoxins, T-2 toxin, HT-2 toxin, nivalenol, deoxynivalenol (DON), and other fusariotoxins, such as fumonisins [ 1 ]. Many mycotoxins are known in our environment, which can be carcinogenic, hepatotoxic, and nephrotoxic in humans and animals [ 2 ]. Trichothecene mycotoxins and fumonisins can induce subchronic and subclinical symptoms in farm animals, such as growth retardation, feed refusal, impaired production traits, increased mortality, and increased sensitivity to infectious diseases due to improper immune responses and less effective vaccination [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corn is an important component of poultry feed commonly contaminated with Fusarium molds, thus potentially exposing laying hens to trichothecene mycotoxins, T-2 toxin, HT-2 toxin, nivalenol, deoxynivalenol (DON), and other fusariotoxins, such as fumonisins [ 1 ]. Many mycotoxins are known in our environment, which can be carcinogenic, hepatotoxic, and nephrotoxic in humans and animals [ 2 ]. Trichothecene mycotoxins and fumonisins can induce subchronic and subclinical symptoms in farm animals, such as growth retardation, feed refusal, impaired production traits, increased mortality, and increased sensitivity to infectious diseases due to improper immune responses and less effective vaccination [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AFB1 content in contaminated samples from various countries significantly varies. For example, the contamination of wheat and corn grain at the levels exceeding 30 µg/kg is often reported [ 10 , 61 , 62 , 63 ], and sometimes the maximum revealed AFB1 content can exceed 4 mg/kg [ 64 ]. Based on this information, we tested the obtained recombinant AFO on grain samples with the AFB1 content ranging from 33 to 1080 µg/kg and demonstrated that the enzyme can be effective even in the case of extremely high grain contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the different approaches developed for the prevention of and reduction in food and feed pollution with aflatoxin B1 (AFB1) [ 1 , 2 , 3 , 4 , 5 , 6 ], this widespread and very carcinogenic mycotoxin [ 7 , 8 ] continues to be a major concern as a contaminant of various feeds, including wheat, corn and other cereals [ 9 , 10 ]. Cereal grain and its primary processing products constitute the bulk of feed rations for many farm animals [ 11 ], especially monogastric ones, including poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus flavus is a microorganism toxic to humans and animals that has the ability to colonize various food products. Its harmfulness is associated with the production of aflatoxins [ 125 , 126 , 127 ]. Strong antibacterial and antifungal, and even antioxidant effects were associated with substances present in the polysaccharide extract [ 21 ].…”
Section: Fruiting Bodies Of Laetiporus Sulphureus ...mentioning
confidence: 99%